Multiple pleural nodules diagnosed as IgG4-related disease: a case report - Yoshihito Iijima; Shun Iwai; Nozomu Motono; Katsuo Usuda; Akihiro Shioya; Shingo Takeuchi; Shigeki Yamagishi; Kiyoshi Koizumi; Sohsuke Yamada; Hidetaka Uramoto (Surgical Case Reports)
Abstract Background Immunoglobulin G4 (IgG4)-related diseases are characterized by abnormal IgG4 levels, swelling, and marked infiltration and fibrosis of the lymphocytes and IgG4-positive plasma cells, causing hypertrophic lesions or nodules. The cause is currently not well understood. IgG4-related diseases involving lesions limited to the pleura are extremely rare. Herein, we report an IgG4-related disease presenting with multiple pleural nodules confirmed by thoracoscopic surgical biopsy. Case presentation A 74 year-old man was referred to our department for definitive diagnosis of multiple pleural nodules after 1 year of follow-up. Computed tomography of the chest revealed multiple pleural nodules, while 2-deoxy-2-( 18F)-fluorodeoxyglucose positron emission tomography imaging exhibited tracer accumulation in the nodules. A thoracoscopic surgical biopsy was performed. Histopathological examination revealed hyalinized fibrous tissue with a high degree of plasma cell-based inflammatory cell infiltration. Immunohistochemically, IgG4-positive cells were conspicuous, accounting for 70.5% of the plasma cells. The postoperative serum IgG4 concentration was 289 mg/dL. We diagnosed the patient with an IgG4-related disease with multiple pleural nodules. The postoperative course was good, and the patient is currently being followed up. Conclusion IgG4-related disease should be considered in cases presenting with multiple pleural nodules.